The Code of Ethical Conduct of the University of Maribor / Kodeks etičnega ravnanja Univerze v Mariboru - Pahor, Dušica (Acta Medico-Biotechnica, 2022)
On July 06, 2021 the Senate of the University of Maribor adopted the Code of Ethical Conduct of the University of Maribor. Having adopted the new document, the Code of Professional Ethics of the University of Maribor from the year 2015 and theCode of Ethics and Integrity for Researchers at the function. The Code of Ethical Conduct is a general act of the University of Maribor, and it is binding for all the university's workers and students ...